2015
DOI: 10.1002/ardp.201500031
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Triplets with a 1,3,5‐Trioxazatriquinane Skeleton and Their Pharmacologies for Opioid Receptors

Abstract: We designed and synthesized novel triplet molecules with 1,3,5-trioxazatriquinane skeletons. One class comprises double-capped triplets with a morphinan skeleton; the other class comprises simple phenol derivatives with phenethylamine moieties. One compound with m-phenolic hydroxyl group, called SYK-146, is a highly selective, potent agonist for the κ receptor, with activity nearly equivalent to that of U-50488H. The o-phenolic isomer of SYK-146, called SYK-524, showed potent but non-selective agonistic activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…The opioid ligands bind with opioid receptors with three main types of pharmacophore bonds: ionic attraction, π–π interaction, and hydrogen bonding, termed the message site . The above obtained potent OX 1 R antagonists were hardly bound with the opioid receptors because of the absence of the basic nitrogen and the phenolic hydroxy group. ,, The ion formed by the protonation on the basic 17-nitrogen and the acidic hydrogen derived from the 3-phenolic hydroxyl group seemed to disrupt the fitting to the orexin receptor.…”
Section: Results and Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The opioid ligands bind with opioid receptors with three main types of pharmacophore bonds: ionic attraction, π–π interaction, and hydrogen bonding, termed the message site . The above obtained potent OX 1 R antagonists were hardly bound with the opioid receptors because of the absence of the basic nitrogen and the phenolic hydroxy group. ,, The ion formed by the protonation on the basic 17-nitrogen and the acidic hydrogen derived from the 3-phenolic hydroxyl group seemed to disrupt the fitting to the orexin receptor.…”
Section: Results and Discussionmentioning
confidence: 98%
“…The only 17-Boc derivative 26 had a rather higher affinity for the KOR ( K i = 184 nM) despite containing the 3-methoxy group. These data from the binding assays suggest that the above obtained 3-methoxy­sulfonamide derivatives could remove the serious side effects derived from the opioid receptors (addiction, constipation, respiratory depression from MOR, catalepsy from DOR, and especially sedation and aversion from KOR), although the structures of these OX 1 R antagonists were derived from the potent KOR agonist, nalfurafine ( 12 ) …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8] Several strategies have been reported to assemble these heterocyclic motifs which include: [3 + 2]-annulation reactions, 9,10 1,3-dipolar cycloaddition, 11,12 the condensation reaction of 1,2-amino alcohol/diamine derivatives with carbonyl compounds, 5,13,14 the aza-Wacker reaction, 15 etc. In 2011, Xiao et al reported sp 3 C-H bond functionalisation of the N-CH 2 Ph (benzylic) group and subsequent intramolecular cyclisation of 1-2-diamines using a Ru-based photocatalyst in the presence of a strong base (Fig. 2a).…”
Section: Introductionmentioning
confidence: 99%
“…16 The cyclisation of amines and amino alcohols has emerged as an attractive approach to synthesize imidazolidines, fused-imidazolines and oxazolidines. [16][17][18][19] The synthesis of the above heterocyclic motifs via selective sp 3 C-H bond functionalisation of the N-Me (alkyl) group is considered a challenging task due to its high thermodynamic stability. 20 Most of the above strategies involve the use of expensive metal complexes, reactive oxidants and elevated temperature (Fig.…”
Section: Introductionmentioning
confidence: 99%